2018
DOI: 10.1007/s10661-018-6678-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of rotifers in microzooplankton community in a large monsoonal estuary (Cochin backwaters) along the west coast of India

Abstract: The distribution ecology of microzooplankton in the Kochi (Cochin) backwaters has been presented. Emphasis has been given to the micro-rotifers present in the environment, considering they were a hitherto ignored component of the microzooplankton in the past studies. Three seasonal samplings were carried out at six locations along the salinity gradients in the Kochi backwaters during the Pre-Monsoon (March), Southwest Monsoon (August), and Northeast Monsoon (December). A total of 48 species of microzooplankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our results showed that in an urban river with underground saline mine water discharge (the Bolina River), the highest number of rotifer species was represented by the genus Brachionus. A similar relationship has been observed in naturally and anthropogenically saline rivers and water reservoirs (including estuaries and lakes) (Modenutti and Claps, 1988;Green, 1993;Neschuk et al, 2002;Arora and Mehra, 2009;Battauz et al, 2013;Anjusha et al, 2018). Similar to the Bolina River, Brachionus species not only dominated in the rotifer communities in the Bolina River but also in the Mossoró River Estuary (Medeiros et al, 2010) as well as in the saline lowland Salado River (Neschuk et al, 2002).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results showed that in an urban river with underground saline mine water discharge (the Bolina River), the highest number of rotifer species was represented by the genus Brachionus. A similar relationship has been observed in naturally and anthropogenically saline rivers and water reservoirs (including estuaries and lakes) (Modenutti and Claps, 1988;Green, 1993;Neschuk et al, 2002;Arora and Mehra, 2009;Battauz et al, 2013;Anjusha et al, 2018). Similar to the Bolina River, Brachionus species not only dominated in the rotifer communities in the Bolina River but also in the Mossoró River Estuary (Medeiros et al, 2010) as well as in the saline lowland Salado River (Neschuk et al, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…By contrast, the value of the Shannon-Wiener index for the rotifer communities of the most saline sections of the Vembanad estuary was higher. However, the value of the H 0 index for the rotifer communities of a large monsoonal estuary (Cochin backwaters) only ranged up to 1.7 (Anjusha et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…They form the basis of the microzooplankton community in the plankton food web and link the energy flow to higher organisms. Recently, a growing number of studies considers rotifers as an indicator of marine pollution and toxicity of plastic nanoparticles [79][80][81], as well as a model species for pharmaceutical and toxicological studies [80,82]. To test the toxicity and uptake efficiency of fluorescent nanoparticles, Brachionus calyciflorus were treated with CdSe/ZnS QD red and IR9-FITC mixed CdSe/ZnS QD red complexes respectively (Figure 2).…”
Section: Survival Rate In Rotifersmentioning
confidence: 99%